Structural Change and Regional Employment Dynamics - Helge Sanner; Uwe Blien (European Regional Science Association (ERSA), 2006)
A casual look at regional unemployment rates reveals that there are vast differences, which appearently cannot be explained by different institutional settings. Our paper attempts to trace the these differences in the regions' labor market performance back to the regions' specialization in products that are more or less advanced in the product cycle. The model we develop shows how individual profit and utility maximization endogenously leads to decreasing employment in the presence of process innovation. Things get even worse if the considered region is less innovative than others. Our model suggests that the only way to escape from this vicious circle is to specialize on products that are at the beginning of their economic life.
Keywords: 330